2019
DOI: 10.1016/j.gloenvcha.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterising climate change discourse on social media during extreme weather events

Abstract: This is a repository copy of Characterising climate change discourse on social media during extreme weather events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 39 publications
4
48
2
3
Order By: Relevance
“…Different frames concerning the global climate concern are popular among the public, politicians, environmentalists, and the media [1,28,29]. Big data analyses have indicated that when interpreting climate events, individuals' preference for frameworks was influenced by demographics [5] and social-political background [2]. Different choices of frameworks can evoke different psychological processes [30], promote or inhibit engagement intentions [31], or gain approval on various levels [32].…”
Section: Climate Change Global Warming and Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different frames concerning the global climate concern are popular among the public, politicians, environmentalists, and the media [1,28,29]. Big data analyses have indicated that when interpreting climate events, individuals' preference for frameworks was influenced by demographics [5] and social-political background [2]. Different choices of frameworks can evoke different psychological processes [30], promote or inhibit engagement intentions [31], or gain approval on various levels [32].…”
Section: Climate Change Global Warming and Framesmentioning
confidence: 99%
“…The public's distinct understanding of the cause and effect of the global climate issue is an obstacle to joint mitigation actions. In addition to a diversity of views co-existing in the public discourse [1,2], previous studies noticed that the public had even failed to reach an agreement on whether "climate change" or "global warming" is the most appropriate definition of the global climate concern [3][4][5]. According to the definition provided by [6], global warming describes global climate issues as a continuous increase in the average temperature of Earth's surface due to anthropogenic emissions of greenhouse gases, whereas climate change includes not only temperature rise but also a range of complex changes in the state of the climate [7], which may be caused by natural process, external forces, or human interventions [8].…”
Section: Introductionmentioning
confidence: 99%
“…One such topic is Climate Impacts in the Pacific as compared to the Southeast. These regions have recently experienced a disproportionate number of natural disasters [ 32 , 33 ] which has been previously shown to influence climate change beliefs of a region [ 4 , 5 ]. Similarly, Environmental Justice emerges as an important topic in the Rockies, Southeast, Southwest, and Northeast.…”
Section: Resultsmentioning
confidence: 99%
“…This is complicated by geographic variations in climate change belief in the United States, where county-level belief in climate change ranges from 43-80% of the population [ 1 ]. These variations have been attributed to endogenous factors such as regional heterogeneity in racial and ethnic composition [ 1 ], media consumption [ 2 ], and the beliefs of an immediate social circle [ 3 ]—as well as exogenous factors such as the frequency of exposure to natural disasters [ 4 , 5 ] and geographic proximity to the coast [ 6 ]. Understanding causes of variation in climate change opinions requires a holistic analysis of the topics, themes, and events associated with climate change beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…"Listening in" on conversations is to some extent made possible by examining social media activity. Social media channels have become increasingly influential in exchanging information, mediating discussions on topical issues, and giving users the opportunity to create their own stories or share opinions (Roxburgh et al, 2019). The open exchange of contrasting perspectives provides rich material to study the communication of contested topics within or across groups (e.g.…”
Section: Introductionmentioning
confidence: 99%